Creole goat morphological diversity partially mirrors district-level variation in the seasonally dry forest of Piura in Peru - José Antonio Haro-Reyes; Emmanuel Alexander Sessarego; Danny Julio Cruz; Pablo R. Gonzales-Guevara; José Antonio Ruiz-Chamorro; Juancarlos Alejandro Cruz-Luis (PLoS ONE, 2025)
Livestock systems in marginal ecosystems such as seasonally dry forests (SDFs) face increasing sustainability challenges, yet the role of morphology in mediating animal adaptation to local environmental and management conditions remains underexplored. In the Piura region of northern Peru—home to the country’s most extensive SDF and its leading hub of goat production—Creole goats represent a diverse and under-characterized resource shaped by natural and human selection. Despite Creole goats’ relevance, little is known about the spatial structure of their phenotypic variation or how it may signal emerging regional morphotypes. Addressing this gap, we conducted a comprehensive morphometric analysis of 617 female Creole goats across three distinct districts within Piura’s SDF. Using linear body measurements (LBMs), morphometric indices, and multivariate analyses, we revealed significant district-level phenotypic differentiation. Goats from Catacaos exhibited consistently larger body dimensions and higher compactness indices, forming a distinct cluster in hierarchical analyses and suggesting the emergence of a localized morphotype. Notably, this phenotypic pattern was largely driven by animals from four specific farmers, pointing to the potential influence of herd-level management practices or breeding history. Despite this within-district heterogeneity, the Catacaos subgroup remained clearly differentiated from goats in Lancones. Principal component analysis of LBMs identified a dominant size axis explaining over 70% of variance, with Catacaos goats diverging along this dimension. In contrast, morphometric indices showed weaker discriminatory power. These findings suggest that LBMs outperform derived indices in capturing fine-scale phenotypic structure and may reflect both ecological adaptation and management-driven selection. Our results underscore the potential of morphometric profiling for identifying regionally adapted livestock types and lay the groundwork for future geographic indication schemes that valorize local biodiversity and support rural livelihoods.